Comparison of Long and Short High-Intensity Interval Exercise Bouts on Running Performance, Physiological and Perceptual Responses - Valstad, Sverre Andre; von Heimburg, Erna; Welde, Boye; van den Tillaar, Roland (Sports Medicine International Open, 2018)
This study compared the effects of long (4×4 min) and short intervals (4×8×20 s) of high-intensity interval exercise bouts (HIIT) on running performance, physiological and perceptual responses, and excess postexercise oxygen consumption (EPOC). Twelve healthy college students (8 men, 4 women; mean age=22±2 years) performed long (90–95% of peak heart rate) and short intervals (maximal intensity) of high-intensity training (running on a non-motorized treadmill) with the same total duration on separate days. The total volume of consumed oxygen during recovery was the same in both cases (P=0.21), whereas the short intervals of high-intensity training were performed at a faster mean running velocity (3.5±0.18 vs. 2.95±0.07 m/s) and at a lower RPEbreath compared with the long intervals of high-intensity training. The blood lactate concentration also tended to be lower during the short intervals of high-intensity training, indicating that short-interval training was perceived to be easier than long-interval training, even though the cardiovascular and metabolic responses are similar. Furthermore, EPOC lasted significantly longer (83.4±3.2 vs. 61.3±27.9 min, P=0.016) and tended to be higher (8.02±4.22=vs. 5.70±3.75 L O2, P=0.053) after short intervals than after long intervals of training.
Keywords: accumulated oxygen uptake; aerobic exercise; postexercise metabolism; resting metabolic rate